2014
DOI: 10.5812/ircmj.14627
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors and O-Serogroups Profiles of Uropathogenic Escherichia Coli Isolated from Iranian Pediatric Patients

Abstract: Background:Uropathogenic Escherichia coli O- Serogroups with their virulence factors are the most prevalent causes of UTIs.Objectives:The present investigation was performed to study the virulence factors and O-Serogroups profiles of UPEC isolated from Iranian pediatric patients.Patients and Methods:This cross sectional investigation was performed on 100 urine samples collected from hospitalized pediatrics of Baqiyatallah Hospital, Tehran, Iran. Midstream urine was collected to decrease potential bacterial, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…Momtaz et al (2013) 8 represented that set1, fim, cnf1, papGIII and hlyA were the most commonly detected virulence factors in the UPEC strains of patients suffered from UTIs which was entirely similar to our findings. High prevalence of fim, hly, sfa, afa and also various types of pap genes were also reported by Dormanesh et al (2014) 15 24 . These genes are mainly associated with adhesion, colonization and invasion of bacterial strains into the urinary epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Momtaz et al (2013) 8 represented that set1, fim, cnf1, papGIII and hlyA were the most commonly detected virulence factors in the UPEC strains of patients suffered from UTIs which was entirely similar to our findings. High prevalence of fim, hly, sfa, afa and also various types of pap genes were also reported by Dormanesh et al (2014) 15 24 . These genes are mainly associated with adhesion, colonization and invasion of bacterial strains into the urinary epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…All of the positive colonies were confirmed using the polymerase chain reaction (PCR) technique (15). PCR was performed with a total volume of 50 µL including 2 mM MgCl2, 1 µM of forward primer (5'-AGAGTTTGATC MTGGCTCAG-3'), 1 µM of reverse primer (5'-CCGTCAATTCATTTGAGTTT-3'), 5 µL PCR buffer 10X, 200 µM dNTP (Fermentas), 1 U Taq DNA polymerase (Fermentas) and 2.5 µL DNA template.…”
Section: Dna Extraction and E Coli Identificationmentioning
confidence: 99%
“…3,4 Resistant bacteria caused more severe clinical diseases for longer period of time which causes abundant economic losses. [1][2][3][4] Documented data revealed that pathogenic bacteria and especially Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), Bacillus cereus (B. cereus), Pseudomonas aeruginosa (P. aeruginosa), Listeria monocytogenes (L. monocytogenes), Klebsiella pneumoniae (K. pneumoniae) and Salmonella typhi (S. typhi) exhibited the high levels of resistance against aminoglycosides, tetracyclines, lincosamides, macrolides, beta-lactams, quinolones, fluoroquinolone and cephems groups of antibiotics. [1][2][3][4][5][6][7][8] Therefore, therapeutic and pharmacological factories tried to use from novel sources for antimicrobial agents to produce strong antibiotic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of severe levels of the antibiotic resistance is the main issue facing medical practitioners. 1,2 Antimicrobial resistance threatens the effective prevention and treatment of an ever-increasing range of infections caused by bacteria. It is an increasingly serious threat with global public health impact that requires action across all government sectors and society.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] UTIs is an important cause of mortality and morbidity alaround the world. 5,6 Pseudomonas aeruginosa (P. aeruginosa) is a non-fermentative, aerobic, Gramnegative rod shape bacterium and is responsible for severe human clinical infections such as BIs, UTIs, pneumonia, wound, reproductive tract, respiratory tract and superficial and gastrointestinal infections, cystic fibrosis, ecthyma gangrenosum and black necrotic lesions. 7 It is also related to sever cases of hospital-acquired and healthcare associated infections globally.…”
Section: Introductionmentioning
confidence: 99%